1987
DOI: 10.3109/00365528708991493
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac Proctitis

Abstract: An increased association of ulcerative colitis and coeliac disease has been reported, as have the results of several small-bowel biopsy studies in ulcerative colitis. Forty-two patients from a population of 438 patients with coeliac disease had rectal biopsies. Fourteen of these showed inflammation of various degrees of severity, including three compatible with a diagnosis of ulcerative colitis. The presenting complaint in 34 of these patients was diarrhoea or steatorrhoea. Twenty-seven patients had coeliac di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…31 32 Cellier et al found that a gluten free diet induced regression but not normalisation of T cell activation in the rectal mucosa of patients with coeliac disease. 32 Their report together with our present results suggests a non-gluten related increase in the inflammatory propensity of the gut mucosa in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…31 32 Cellier et al found that a gluten free diet induced regression but not normalisation of T cell activation in the rectal mucosa of patients with coeliac disease. 32 Their report together with our present results suggests a non-gluten related increase in the inflammatory propensity of the gut mucosa in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although based strictly on the twin pair studied herein, this finding is nonetheless of interest in light of prior reports indicating that coeliac disease patients also have increased numbers of / IEL in the rectal mucosa [46]. Although mucosal damage in coeliac disease is generally confined to the proximal small intestine [3], proctitis and lymphocytic colitis have been noted in some coeliac disease patients [47,48] and, compared with healthy individuals, the rectal mucosa of coeliac disease patients has been reported to respond abnormally to experimental gluten challenge [49,50]. Thus, taken together, these studies suggest an underlying abnormality may affect the entire intestinal mucosa in coeliac disease.…”
Section: Discussionmentioning
confidence: 57%
“…The coexistence of CD with Crohn's disease and UC has since been described in several case reports. 6,12,13 In 1987, Breen et al 7 reviewed 42 rectal biopsies from a population of 438 patients with CD and found 3 patients with abnormal rectal biopsy results who had histopathologic and clinical features of UC. An epidemiological survey of IBD in the firstdegree relatives of 162 celiac patients showed the relative risk of IBD to be five times greater for firstdegree relatives than for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The first association of celiac disease (CD) and UC was reported over 30 years ago by Salem and Truelove. 4 Since that publication, several authors have described an association of CD and UC, [5][6][7][8][9][10][11][12][13] although most of the reports are simply case reports; accordingly the clinical significance of this association is not yet established.…”
Section: Introductionmentioning
confidence: 99%